Cross-Sector Relational Realignments after an Institutional Crisis: Checking the Instrumentalization of Corporate-Nonprofit Partnerships - Gama, Marina A. B.; Gatignon, Aline (Academy of Management Journal, 2025)
We examine how government corruption scandals influence corporate-nonprofit partnerships by altering the institutional context in ways that reshape the value of nonmarket relationships. We analyze these dynamics following Operation Carwash (2014) in Brazil, using comprehensive data on all publicly listed firms and registered nonprofits from 2010 to 2017. We find that partnerships became more common after the scandal’s disclosure, as firms and nonprofits sought to collaborate on socioeconomic development. However, firms seen as directly or indirectly implicated in the scandal struggled to form partnerships due to risks to nonprofits’ legitimacy. Moreover, nonprofits perceived as closely aligned with firms (i.e., trade associations) or the state (i.e., education and research nonprofits or those with political capital) were especially cautious about entering partnerships to avoid appearing complicit in advancing corporate political influence. Our findings thus “check” the instrumentalization of corporate-nonprofit partnerships in two ways: by examining how it unfolds after an institutional crisis and by revealing how nonprofits resist being used as vehicles for corporate reputational repair or political gain. We show that such crises can trigger a broader realignment of corporate partnerships with nonmarket actors, highlighting the need to study shifts across nonmarket sectors, and not just within them.